“Genotoxicidad del ADN y anemia en sangre de policías de tránsito de la ciudad de Trujillo-2018.” - Alegría Zumaeta, Jackelyn (2019)
ABSTRACT There is no doubt that pollution affects population health in many ways, depending on the pollutant that is most present in the environment. Thus, this investigation was successful in determining if the concentration of air pollutants in the city of Trujillo affects the health of the population in general and, in particular, of traffic police officers who are permanently exposed; through the test of damage to DNA and blood levels of anemia. DNA damage was evidenced through the comet assay and blood anemia levels, through hemoglobin values. Two groups of traffic police officers were taken as sample. The white or control group was formed by police officers with a service time of less than 6 months and the problem group by police officers with more than 2 years of service. The problem group was who obtained the highest percentage of DNA in the tail, with an average of 13.04%, compared to the average of the control population of 9.48%; that is, with a marked significant difference; demonstrating a direct relationship between the increase in damage to DNA by the exposure time of the policemen to the contamination. However; no evidence of anemia levels was found in both populations. Therefore, it is concluded that there is damage to the health of police officers due to exposure to air pollution in the city; with this we corroborate that the assay is appropriate to assess environmental risks and damage to DNA.